Are Skincare Brands Turning Gen Z’s Loyalty into Profitable Ventures in Africa? A PLS-SEM Analysis of Deceptive Marketing Practice on Consumer Behaviour - Abdulsalam, Tajudeen Alaburo; Tajudeen, Rofiat Bolanale (ABUAD Journal of Social and Management Sciences, 2024)
The skincare market reached 154.4 billion in 2023, with projected growth of 262.5 billion in 2032 at a 6.0% growth rate. This led skincare brands to compete for dominance, using deceptive marketing tactics in advertising, labelling, product ideas, and packaging. Despite short-term financial gains, deceptive marketing practices have neglected people and planet considerations. Gen Z, raised by world-marked environmental concerns, prioritises social activism and environmental sustainability in their purchasing behaviour. The Internet has amplified these trends, disseminating deceptive ideas widely and leading to consumer confusion and complex purchase decisions. The study explored how skincare brands exploit Gen Z’s loyalty for profitability by assessing the impact of deceptive marketing on consumer purchasing decisions in the cosmetics industry. The study conducted an online survey targeting Gen Z skincare consumers in economically diverse African countries, including Egypt, South Africa, Morocco, Nigeria, Uganda, and Lesotho, obtaining 352 responses worth 92% of the sample size. The survey, analysed using the PLS-SEM approach, showed high predictive power between research variables, with R2 coefficients of 55.1% for Gen Z’s loyalty and 5.9%, 6.9%, and 5.6% for advertising, labelling and packaging, and product ideas, exceeding the 5% threshold. Findings suggest deceptive marketing impacts Gen Z’s loyalty as a measure of purchase behaviour in Africa’s cosmetics industry. Research recommends prioritising ethics in marketing practices, developing unique labelling and packaging, enforcing regulations, and investing in consumer education to empower consumers to make informed decisions. The study notes biases in data collection due to unequal online access among Gen Z consumers.